2016
DOI: 10.1021/acs.inorgchem.6b01652
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Bromide to Bromine

Abstract: Three consecutive bimolecular reactions are employed to photocatalyze bromide oxidation to bromine. The system consists of a ruthenium(II) complex, [Ru(deeb)(dmbpy)] (deeb = 4,4'-diethylester-2,2'-bipyridine; dmbpy = 4,4'-dimethyl-2,2'-bipyridine), 4-bromobenzenediazonium tetrafluoroborate (ArNBF), and Br. Varying reagent concentrations allowed us to optimize the sequence of reactions for product formation. The electronically excited ruthenium complex (*Ru) reacts first with ArNBF to produce a ruthenium(III) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…Formation of I 2 during the reaction, confirmed by UV–vis spectroscopy (Figure S3), likely interfered with light absorption by PS. Light-driven formation of halogens from halides utilizing transition-metal chromophores has been previously reported …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Formation of I 2 during the reaction, confirmed by UV–vis spectroscopy (Figure S3), likely interfered with light absorption by PS. Light-driven formation of halogens from halides utilizing transition-metal chromophores has been previously reported …”
Section: Resultssupporting
confidence: 87%
“…Light-driven formation of halogens from halides utilizing transition-metal chromophores has been previously reported. 49 This catalytic system also exhibited functional group tolerance in the homocoupling of alkyl halides. Efficient dimerization was achieved with substrates containing methoxy (95%, reaction 6), methoxycarbonyl (98%, reaction 7), and tert-butoxycarbonyl protected amine (85%, reaction 8).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yun-Da Tsai et al have reported the photocatalytic oxidation of bromide by ruthenium polypyridyl species in acetonitrile solution. , In their early study, photooxidation of bromide was achieved with the [Ru­(deeb) 2 (dmb)] 2+* excited state. However, the second-order rate constant for bromide oxidation k = 2 × 10 6 M –1 s –1 was small, resulting in inefficient excited-state quenching attributed to a small thermodynamic driving force.…”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
“…Excited state electron transfer reactions are central to molecular level approaches to solar energy conversion. Recently hydrohalic acid splitting has re-emerged as a promising target. Hydrobromic acid (HBr) is of particular interest in this regard, eq , as the hydrogen and bromine products are solar fuels amenable to storage in flow batteries , and fuel cells. Here we report bromide photo-oxidation sensitized to visible light with a Ru diimine complex. …”
Section: Introductionmentioning
confidence: 98%